2016
DOI: 10.4028/www.scientific.net/kem.723.94
|View full text |Cite
|
Sign up to set email alerts
|

Study on Equivalent Viscous Damping of Aeolian Vibration for Transmission Line by AACSR-400 Steel Core Aluminum Alloy Wire

Abstract: To ensure its operational security, it is important to study the vibration state of transmission line. The equivalent viscous damping of aero-vibration for a large-span overhead conductor is obligated to be determined. In this paper, the damping characteristics of conductor by AACSR-400 steel core aluminum alloy wire are studied by use of energy balance principle. Based on the Diana wind energy curve and equivalent viscous damping, the relationship between frequency and damping ratio is conducted and discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The study of the vibration state of transmission lines can ensure the safety problem of transmission lines to a certain extent. Zhang, B. et al studied the damping characteristics of the conductor of AACSR-400 copper-core aluminum alloy transmission conductor based on the principle of conservation of energy, analyzed the relationship between the frequency of power transmission and damping, and simulated experiments on the transmission data by using ANSYS, and the study showed that the ANSYS finite element The analysis is consistent with the results of the principle of energy conservation [8]. Fan, W. et al believe that to ensure the safety of transmission lines in the extreme cold region transmission process, taking into account the existence of de-icing robots, to construct a dynamic movement model of multi-span transmission lines, combined with the de-icing robot's trajectory, to classify the icing conditions of the transmission lines in the extreme cold region, to avoid the de-icing robots to the transmission line of the damage [9].…”
Section: Introductionmentioning
confidence: 63%
“…The study of the vibration state of transmission lines can ensure the safety problem of transmission lines to a certain extent. Zhang, B. et al studied the damping characteristics of the conductor of AACSR-400 copper-core aluminum alloy transmission conductor based on the principle of conservation of energy, analyzed the relationship between the frequency of power transmission and damping, and simulated experiments on the transmission data by using ANSYS, and the study showed that the ANSYS finite element The analysis is consistent with the results of the principle of energy conservation [8]. Fan, W. et al believe that to ensure the safety of transmission lines in the extreme cold region transmission process, taking into account the existence of de-icing robots, to construct a dynamic movement model of multi-span transmission lines, combined with the de-icing robot's trajectory, to classify the icing conditions of the transmission lines in the extreme cold region, to avoid the de-icing robots to the transmission line of the damage [9].…”
Section: Introductionmentioning
confidence: 63%
“…In recent years, research on the economic performance of conductors has primarily focused on traditional wire types, such as steel-reinforced aluminum alloy stranded wire conductors [3], steel core aluminum stranded wire [4], expanded-diameter conductors [5] and others. Research involving new wire types has focused primarily on transmission capacity [6], transmission line applications [7], conductor selection methods [8], optimization design of the conductor section selection [9] and other aspects.…”
Section: Introductionmentioning
confidence: 99%